PERENCANAAN INOVASI PENGEMBANGAN AGROWISATA BUKIT FLORA DENGAN PENDEKATAN METODE BISNIS MODEL KANVAS - Hanik, Ummi; Mas'ud, M. Imron (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
Agro-tourism in Indonesia is one of the driving sectors in improving the economy that is in great demand by tourists from both domestic (domestic) and foreign (foreign) countries. There fore there is a need for development in its management, one of which is in the Bukit Flora Agro Tourism. To realize this there needs to be a plan for innovation. The purpose of this study is to identify the strengths, weaknesses, opportunities, and threats of the internal and external environment of the flora hill agrotourism, and determine the innovation plan for the development of flora hill tourism by using the Business Model Canvas approach. The final results of the research are expected to know the strengths, weaknesses, opportunities, and internal and external environmental threats of the flora hill agrotourism, and determine the innovation plan for the development of flora hill tourism